1997
DOI: 10.1093/emboj/16.4.706
|View full text |Cite
|
Sign up to set email alerts
|

Opposite effects of the p52shc/p46shc and p66shc splicing isoforms on the EGF receptor-MAP kinase-fos signalling pathway

Abstract: Shc proteins are targets of activated tyrosine kinases and are implicated in the transmission of activation signals to Ras. The p46shc and p52shc isoforms share a C‐terminal SH2 domain, a proline‐ and glycine‐rich region (collagen homologous region 1; CH1) and a N‐terminal PTB domain. We have isolated cDNAs encoding for a third Shc isoform, p66shc. The predicted amino acid sequence of p66shc overlaps that of p52shc and contains a unique N‐terminal region which is also rich in glycines and prolines (CH2). p52sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
381
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 392 publications
(393 citation statements)
references
References 46 publications
11
381
1
Order By: Relevance
“…In previous studies, we and others have demonstrated that the duration of the MAPK activation determines the e ect of FGF-2 on cell proliferation (Liu et al, 1998;Albas et al, 1998). Moreover speci®c signaling molecules such as Shc, were involved in cell proliferation through regulation of the MAPK pathway (Migliaccio et al, 1997;Kouhara et al, 1997). Interestingly, we show here that p66 Shc is overexpressed in MCF-7ras cells and tyrosine phosphorylated upon FGF-2 treatment.…”
Section: Correlation Of Ras Activity and Fgf-2-induced Dna Synthesismentioning
confidence: 63%
“…In previous studies, we and others have demonstrated that the duration of the MAPK activation determines the e ect of FGF-2 on cell proliferation (Liu et al, 1998;Albas et al, 1998). Moreover speci®c signaling molecules such as Shc, were involved in cell proliferation through regulation of the MAPK pathway (Migliaccio et al, 1997;Kouhara et al, 1997). Interestingly, we show here that p66 Shc is overexpressed in MCF-7ras cells and tyrosine phosphorylated upon FGF-2 treatment.…”
Section: Correlation Of Ras Activity and Fgf-2-induced Dna Synthesismentioning
confidence: 63%
“…The mammalian Shc gene encodes three overlapping proteins with molecular weights of 46 kDa, 52 kDa and 66 kDa Bon®ni et al, 1996;Migliaccio et al, 1997). All three protein products share a carboxy terminal Src Homology 2 (SH2) domain, a central glycine/proline rich domain with homology to alpha1 collagen (CH1), and an amino terminal phosphotyrosine binding (PTB) domain.…”
Section: Introductionmentioning
confidence: 99%
“…The p66 isoform is produced via alternative splicing of the Shc gene and contains an amino terminal extension which encodes a second collagen homology region (CH2) in addition to the common PTB, CH1, and SH2 domains. Interestingly, it has been demonstrated that the expression of p66 is more restricted and some of its biological properties distinct from those of p52 and p46 Shc (Bon®ni et al, 1996;Migliaccio et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…By both alternative splicing and transcription start sites three protein isoforms of 66, 52 and 46 kDa are produced. The Shc p52/46 isoforms are involved in the transmission of signals from activated TKs (Migliaccio et al, 1997), and the Shc p66 isoform controls stress apoptotic responses and life span (Migliaccio et al, 1999). In addition to collagen homology (CH) domains, Shc proteins have phosphotyrosine binding (PTB) and Src homology 2 (SH2) domains (Migliaccio et al, 1997;Pelicci et al, 1992) both involved in exclusive or cooperative binding to phosphotyrosine residues.…”
mentioning
confidence: 99%
“…The Shc p52/46 isoforms are involved in the transmission of signals from activated TKs (Migliaccio et al, 1997), and the Shc p66 isoform controls stress apoptotic responses and life span (Migliaccio et al, 1999). In addition to collagen homology (CH) domains, Shc proteins have phosphotyrosine binding (PTB) and Src homology 2 (SH2) domains (Migliaccio et al, 1997;Pelicci et al, 1992) both involved in exclusive or cooperative binding to phosphotyrosine residues. Upon receptor binding, Shc undergoes phosphorylation at three tyrosine residues (317, 239 and 240), becomes capable of interacting with the SH2 domain of Grb2, and causes the activation of the SOS/Ras/MAPK pathway.…”
mentioning
confidence: 99%